Evaluation of recruitment and retention strategies for effective employee turnover management - Wardhani, Winda; Yanti, Aprilda (Junal Ilmu Manajemen, 2025)
Effective employee turnover management is essential in retaining competent employees in an organization. One strategy that can be done is the right recruitment and retention of employees. The results of this study show that companies need to develop an integrated and sustainable employee recruitment and retention strategy over a long period of time. In an effort to retain employees, companies also need to recognize achievements and provide the training and development needed to improve employee abilities and provide appropriate incentives. In addition, companies must pay attention to a healthy work environment and organizational culture and support and promote work-life balance for employees to build employee satisfaction and commitment. With the right recruitment and retention strategies, companies can improve effective employee turnover management and retain talented and competent employees within the organization.